Fists in the pocket [videorecording (DVD)] - Bellocchio, Marco, 1939-; Castel, Lou, 1943-; Pitagora, Paola; Masé, Marino, 1939- (Criterion collectiion (DVD videodiscs), 2006)
A young man murders members of his family, all who suffer from epilepsy, in order to save his only healthy brother from the burden of caring for them.